As diretivas antecipadas de vontade como resposta do direito ao desafio do pluralismo cultural - Alfeu, Breno Silveira Moura (2021)
The present thesis is centered on the study of Advance Directives of Will within the current social context, focusing on the fact that cultural pluralism is both its distinctive feature and a challenge to the legal system. The aforementioned analysis is developed by a approach of the Right to Life in conjugation of the science of Law with different fields of knowledge, such as anthropology, sociology and philosophy, and allying this to the Brazilian reality. The central concept to make this possible is the observation that life is a minimal understanding of human reality and is the basis of varied perspectives on itself, including its expressions and amplitude in the legal sphere, which converge or diverge continuously, giving rise to social tension and, consequently, a content dissent, or material dissent. And the maintenance of this tension, in face of the Law’s function of being a tool for stabilizing society, produces a challenge to the legal plan regarding how to accommodate it through its normative prescriptions. From this comes the central question that this dissertation seeks to answer: focusing on the Right to Life and on Brazilian society, how can the Law respond to the challenge arising from contemporary multiculturalism? The legal response may be delimited through by specifying a means of procedural consensus that allows the maintenance of the material dissent. The Advance Directives of Will are the hypothesis obtained, since they are a open legal form and adaptable to the designs and subjectivity of their holder, both of which, in turn, are affected by their cultural perspective, including the right to life. The present study aims, therefore, to investigate the validity of this answer through a basic research with an transdisciplinary bias of a quantitative and qualitative approach that makes use of the hypothetical-deductive method applied to theoretical references of Philosophy, Anthropology, Legal Sociology and Law, among which are adopted as main ones Marcelo Neves and Luciana Dadalto. And this is achieved from bibliographic and documental sources in addition to being centered on the technique of monographic investigation.